ChemInform Abstract: Towards Polymetallic Lanthanide Complexes as Dual Contrast Agents for Magnetic Resonance and Optical Imaging. Issue 6 (February 2015) - Debroye, Elke; Parac‐Vogt, Tatjana N.
Abstract Review: 106 refs.